PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN E-LEARNING TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMK RIYADLUL QUR’AN NGAJUM - Azmi, Ulul; Hasanah, Siti Muawanatul (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This research is motivated by the Covid-19 pandemic so schools are recommended to carry out online schools (on the network), therefore online learning media e-learning is related to student learning achievement. The aims of this study were 1) to determine the use of e-learning based learning media (website) at Riyadlul Qur'an Ngajum Vocational School, 2) to determine the effect of e-learning learning media (website) on student achievement at Riyadlul Qur'an Ngajum Vocational School. This research uses quantitative research design with survey correlation method. Data collection uses a questionnaire/questionnaire and documentation on the PTS (Middle Semester Assessment) and PAT (End of Year Assessment) scores, and uses parametric inferential descriptive statistical data analysis, while the hypothesis calculation data analysis technique uses the Person deviation formula to calculate Product Moment correlation. Based on the results of the study with the aim of knowing how to use E-learning-based Learning Media (websites) in the online learning process, namely by accessing the links that have been shared, logging in with their respective passwords, then just selecting the subjects to be studied and the student achievement of SMK Riyadlul Qur'an Ngajum there is an increase after using learning media based on E-Learning and research data with NORMAL distribution after testing the data received through the normality test and product moment correlation test with the results of the normality test results with a significance result of 0.23 > 0.05 and the results of the correlation test with the value of r count > 0.165, namely 0.172 > 0.165 on the PTS value and 0.181 > 0.165 on the PAT value.